Observation of oxygen vacancy migration in memory devices based on ZnO nanoparticles - Li, Cheng; Vaynzof, Yana (Journal of applied physics, 2017)
We investigate the mechanism of resistive switching in non-volatile memory devices based on an ITO/ZnO nanoparticles/Al structure using electroabsorption (EA) spectroscopy and X-ray photoelectron spectroscopy (XPS). By incorporating a small amount of low-bandgap organic semiconductor, poly(9,9-dioctylfluorene-co-benzothiadiazole) (F8BT), as a probe molecule for EA characterization, we study the change in the built-in potential during the switching process under different ambient conditions. We compare the concentrations of oxygen vacancies between the Al/ZnO interface and the bulk of the ZnO nanoparticle film by XPS. We also investigate the effect of an external electrical field on the concentration of oxygen vacancies at the Al/ZnO interface. We find that the resistive switching can be attributed to the migration of oxygen vacancies driven by the electrical field, accompanied by adsorption/desorption of oxygen molecules at the Al/ZnO interface. This process gives rise to the formation of a dipole layer, which modulates the injection barrier, and is responsible for switching the resistance state of the memory device.
Gesehen am 12.09.2018